Molecular genetics of arrhythmogenic right ventricular and dilated cardiomyopathy in South Africans - Mbele, Mzwandile (Department of Medicine, 2016)
Introduction: Little is known about the molecular genetics of cardiomyopathy in Africans. Aims: to (I) determine the prevalence of desmosomal gene mutations in arrhythmogenic right ventricular cardiomyopathy (ARVC) and dilated cardiomyopathy (DCM) in desmosomal protein genes (i.e., plakophilin 2, desmocollin 2, desmoglein 2, and plakoglobin), (2) establish the presence of a founder effect in families with a recurrent mutation in the plakophilin 2 (PKP2) gene, (3) investigate whether single nucleotide polymorphisms found in desmosomal genes affect gene expression, and (4) search for new candidate genes for ARVC in families where no causal mutation was found in desmosomal protein genes. Methods: 177 participants with cardiomyopathy were screened for desmosomal gene mutations which were confumed by Sanger sequencing. The following methods were used: in the founder effect study we used haplotyping with microsatellite markers; for total gene expression we used real time polymerase chain reaction and allelic expression imbalance and exome sequencing was used for mutation screening in two siblings with severe early onset ARVC. To all novel variants identified prediction tools were used to predict the pathogenicity of the variant in uestion. Results: 21.5% of ARVC pro bands had a disease-causing mutation in one of four desmosomal genes; no disease-causing mutation was found in the 112 OCM index cases. A recurrent PKP2 mutation occurred on a common haplotype background in four white South African probands with cardiomyopathy. Investigation of a common PKP2 polymorphism had no effect on total gene expression nor was there evidence of allelic expression imbalance. Finally, rare mutations were found in PARVA and HMGXB3 by exome sequencing of two siblings.